Enhancing Operations for Sustainability in Indonesian SMEs through Climate Change Awareness and Business Orientation - Hafiz Rahman; Sri Oktavia; Niyanta Shetye; Winny Leocade Sedjiro Azonhoumon (Jurnal Optimasi Sistem Industri, 2024)
This study aims to identify the level of climate change awareness among small-medium scale entrepreneurs (SMEs) and to investigate its impact on future business orientation, with individual self-perception acting as a mediating variable. Addressing a significant gap in the literature, this research explores the reciprocal influence between SMEs and climate change—an area previously underexplored. Conducted in West Sumatra, Indonesia, this study employs a quantitative causal analysis approach using Structural Equation Modelling-Partial Least Squares (SEM-PLS) for robust analysis. The findings indicate that while awareness and self-perception of climate change among SMEs are low, they significantly influence potential changes in business orientation. The study reveals that although many SMEs possess a high level of educational attainment, this does not necessarily translate into heightened awareness or self-perception regarding climate change. This disconnect underscores the critical role of tailored educational initiatives and support systems to bridge the gap between knowledge and action. Additionally, the study finds that SMEs often prioritize immediate financial stability over long-term environmental sustainability, driven by the necessity to meet daily operational demands. These results underscore the urgent need for pre-emptive government policies to guide SMEs toward sustainable practices. Effective interventions should include financial incentives, technical assistance, and educational programs designed to enhance climate change awareness and capabilities among SMEs. Furthermore, this study contributes to the field of industrial engineering by identifying opportunities to optimize SME operations. By integrating environmental sustainability into business strategies, SMEs can enhance their resilience and competitiveness while contributing to broader environmental goals. This research advances the understanding of the dynamic interplay between SMEs and climate change, providing a foundation for future studies aimed at promoting sustainable industrial practices.